A life in Science: In memory of Jean-Pierre Badiali - D. di Caprio; Dong, W.; Henderson, D.; Holovko, M. (Condensed Matter Physics, 2017)
This issue is devoted to the memory of Jean-Pierre Badiali who passed away on April 15, 2016. His death is a great loss to all of us and to the whole scientific community. We express our deepest condolences to the family of Jean-Pierre Badiali, colleagues and friends. Jean-Pierre will remain in our memory as an outstanding scientist and an incredibly amiable person.